Training on Using the Mendeley Application for Students in Writing Bibliography - A. Noer Chalifah Ramadhany; Rusmala Dewi Kabubu; Tiara Nur’aini; Gio Folanda (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2024)
Writing references is often an obstacle for students in writing scientific papers. Including references is very important to avoid plagiarism. In writing scientific papers, students need a lot of references, so it is natural that they make a bibliography manually. Therefore, the Mendeley application is needed which can facilitate the preparation of the bibliography automatically. However, there are still many students who do not understand its use and do not even know the Mendeley application. This training is held online using the zoom application, with the target participants being new students of the sociology education study program who want to know how to use a practical application called Mendeley so that they can an automatic bibliography. This training is a forum for activities that have the aim of helping students so that they can independently manage their bibliography properly. By doing so, it is necessary that the quality of education in Indonesia also increase. This training is also needed to provide maximum output, including increasing the knowledge and understanding of participants in using the Mendeley application, and increasing the skills of participants in using the Mendeley application to work on various forms of scientific writing such a journals, theses, and final assignments.